2021
DOI: 10.5223/pghn.2021.24.5.492
|View full text |Cite
|
Sign up to set email alerts
|

Immunogloboulin E-Mediated Food Sensitization in Children with Celiac Disease: A Single-Center Experience

Abstract: Purpose Celiac disease (CD) is an autoimmune disorder of the small intestine caused by an abnormal immune response to gluten proteins and is often characterized by gastrointestinal symptoms. Food allergy (FA) is an adverse immune sensitivity to ingested food proteins leading to inflammation in various organs including the gastrointestinal tract. The relationship between CD and FA remains unclear. This study aimed to assess the prevalence and clinical relevance of immunoglobulin E (IgE)-mediated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 27 publications
1
26
0
2
Order By: Relevance
“…An analysis of six original studies ( Table 2 ) revealed a possible coexistence of CD and A-IgE in four of them; however, two of them did not confirm this correlation. Among the papers confirming the possibility of an A-IgE occurrence in subjects with CD, two papers concerned allergies [ 14 , 15 ] and another two concerned sensitization [ 12 , 16 ]. Among the studies included in the analysis, there were four prospective [ 14 , 15 ] and two retrospective research studies [ 12 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An analysis of six original studies ( Table 2 ) revealed a possible coexistence of CD and A-IgE in four of them; however, two of them did not confirm this correlation. Among the papers confirming the possibility of an A-IgE occurrence in subjects with CD, two papers concerned allergies [ 14 , 15 ] and another two concerned sensitization [ 12 , 16 ]. Among the studies included in the analysis, there were four prospective [ 14 , 15 ] and two retrospective research studies [ 12 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the papers confirming the possibility of an A-IgE occurrence in subjects with CD, two papers concerned allergies [ 14 , 15 ] and another two concerned sensitization [ 12 , 16 ]. Among the studies included in the analysis, there were four prospective [ 14 , 15 ] and two retrospective research studies [ 12 , 16 ]. Five of the six studies were conducted in Europe [ 12 , 14 , 15 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Allergic children age range 1 to 10 years old from many clinics in Al-Najaf City, Iraq. The pediatric penal kit Polycheck®-Diagnostics (Germany) was used to reveal to the sensitivity of 20 different allergens (9) : Peanut, milk, egg white, egg yolk, potatoes, carrot, cod fish, apple, soya beans, wheat flour, birch pollen, timothy grass pollen, mugwort pollen, D. pteronyssinus, D. Farinae, dog epithelia, cat epithelia, horse epithelia and Cladosporium harbarum. Table (1) showed test measurement the concentration in (Ku/L) for IgE antibodies against any of the above allergens and the concentrations then converted into scores according.…”
Section: Patients and Methods Subjects In The Studymentioning
confidence: 99%